Cooperative Unit Systems: 3. Swine Facilities - Alyssa Schortinghouse (EDIS)
Facilities are one of the most important considerations for housing market swine projects in groups. This 5-page document discusses basic facilities requirements, weather protection, spacing requirements, penning arrangements, and fencing materials. Written by Alyssa Schortinghouse, and published by the UF/IFAS 4-H Youth Development Department, September 2020.